Construction of plasmids for expression of Rous sarcoma virus transforming protein, p60src, in Escherichia coli. - Gilmer, T M (1982)
We have constructed plasmids that direct the synthesis of the Rous sarcoma virus transforming gene (src) product (p60src) in Escherichia coli. A 203-base-pair lac promoter-operator DNA encoding the first eight amino acids of beta-galactosidase was ligated to the 5' end of the src gene from the Prague A strain of Rous sarcoma virus (PrA-RSV) which had been cloned in pBR325. Antiserum, from a tumor-bearing rabbit, directed against pp60src was used to screen bacteria containing the recombinant plasmid for a protein of approximately 60,000 daltons, and several colonies producing a protein immunologically related to pp60src were detected. Partial proteolytic cleavage analysis revealed that the src-related protein produced in bacteria is structurally similar to pp60src immunoprecipitated from PrA-RSV-infected chicken cells. Partially purified src protein from E. coli can be phosphorylated in vitro by the catalytic subunit of cAMP-dependent protein kinase. Tryptic phosphopeptide analysis demonstrated that the catalytic subunit phosphorylated a serine-containing tryptic peptide in the bacterial src protein that comigrated with the phosphoserine-containing tryptic peptide of pp60src immunoprecipitated from 32P-labeled PrA-RSV-infected chicken cells.